PENGARUH LITERASI KEUANGAN DAN MOTIVASI TERHADAP MINAT BERINVESTASI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Suci Febrina; friyatmi friyatmi (STIE Wiyatamandala, 2023)
This research purpose to determine and analyze 1) The Effect of Financial Literacy on Investment Motivation of Faculty of Economics Students. 2) The Influence of Financial Literacy on Students' Interest in Investing in the Capital Market at the Faculty of Economics 3) The Impact of Investment Motivation on Faculty of Economics Students' Investment Interest This research is quantitative and employs associative methods. With a sample of 98 students, the sampling technique used in this study was proportional random sampling with a random number of members from each sub-population. Data collection methods include documentation and questionnaires. The study's findings indicate that 1) Financial literacy has a significant and significant effect on the investment motivation of economics faculty students,. 2) Financial Literacy has no effect on Investment Interest. 3) Investment Motivation has a significant effect on Interest in Investing.